The Survey of EFL Students' Learning Styles at English Education Study Program - Latuheru, Henry (Program Studi Pendidikan Bahasa Inggris FKIP, Universitas Pattimura Ambon, 2021)
The existing literatures on the significance of learning styles and how they can be utilized to help students in their learning process. The present study was designed to survey the existence of EFL students learning styles in English Education Study Program. Moreover, to explore learning styles of students coming from different genders and academic years. The theoretical framework of this study used VARK learning styles by Fleming. In this study, survey methodology was used using VARK questionnaire The findings showed that students preferred multimodal ways of learning in which most of them were VARK learners. In addition, the difference learning style preferences between genders suggested that males were more uni-modal and bi-modal, while females were more tri-modal, yet both genders also scored high for quad-modal. On top of that, among active academic years the preference showed that juniors tend to have single preference in comparison to the seniors who were quad-modal learners. Lastly, this study has widened the study of VARK in the EFL context by providing information for teachers and curriculum designer to better aware of the existing varieties of learning styles in their pupils. Hence, they can design learning activities that can helps learners in classroom.